The Effectiveness Of Government Regulation Concerning Marriage Recording For Baduy Banten Believers - Muhamad Muslih; Eki Furqon (Nurani Hukum, 2021)
The aim of this research is to know some descriptions of the situation, conditions, circumstances, and realities of population administration management and marriage registration in the Baduy community. Then another goal is to know how the role of the government is to overcome this. The specific target to be achieved from this research is to ensure that the Baduy community can complete their population administration and be more maximal in registering their marriage to the KUA and having a marriage certificate as a manifestation of obedience to Law Number 1 of 1974, especially Article 2 paragraph 1 and paragraph 2 and National Law. For more than 40 years, believers of faith have been discriminated against and cannot legally register their marriage because they have to marry based on one of the religions recognized by the state. A few moments later Joko Widodo issued Government Regulation (PP) Number 40 of 2019 concerning Implementation of Law No. 23 of 2006 concerning Population Administration, one of which recognizes and regulates the procedures for marriage between religious believers. The issuance of this PP eliminates the discrimination that has so far been experienced by believers. Believers of faith experience discrimination to get population services as Indonesian citizens (WNI). This raises various problems in the form of discrimination in making e-ID cards, registration of marriage certificates, and others. The research method used is by using the juridical normative and sociological normative approaches. Juridical Normative in the form of discussion of several laws and regulations made by the government which are enforced to regulate population administration and marriage registration for believers. Sociological Normative Research on law constructs law as a system of statutory regulations that have existed so far constructed in a society's behavior. The research specification used is descriptive analytical which aims to describe, analyze, and systematically analyze certain facts. The data in this study were collected and compiled in a narrative form and then analyzed qualitatively. Sources of data used in this study were obtained from Library Research. This study also uses primary and secondary data sources which are analyzed using qualitative methods, with data collection techniques from literature studies and field studies to Baduy. Interviews and observations were conducted to obtain the necessary data. The results of the study show that Government Regulation Concerning Marriage Recording For Baduy Banten Believers has not been effective. Socialization from all parties regarding this Government Regulation to the KUA leader of the Ciboleger area and the Banten Baduy people must be carried out because even though the government has facilitated Population Administration and marriage registration for believers in Government Regulation Concerning Marriage Recording For Baduy Banten Believers, in reality this has not been effective.